Formation of a modern concept of technology park activities - Kosovskiy, Аndrew A. (Journal of the Belarusian State University. Economics, 2024)
Among all modern types of innovation infrastructure entities, technology parks are of greatest scientiﬁc and practical interest. Currently, in diﬀerent countries of the world, the understanding and, accordingly, the deﬁnition at the legislative level of the main tasks and functions of technology parks vary signiﬁcantly. The article proposes a modern concept of a technology park, including the purpose of its operation, tasks and mechanisms for its implementation. It has been revealed that the integral eﬀect for a technology park resident is a combination of the eﬀects of the access provided to them to material resources, the resources of a university or scientiﬁc organisation, an innovation network and a cluster.
Keywords: scientiﬁc and technological park; concept; innovation network; cluster eﬀect